Patai's Chemistry of Functional Groups 2019
DOI: 10.1002/9780470682531.pat0974
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Transformations Involving Organoboron

Abstract: Boron gets its name from the term borax, the mineral from which it was originally isolated, by analogy with carbon due to their chemical similarities. Unlike its neighbor on the periodic table, however, boron only possesses enough valence electrons to form three covalent bonds. This means that organoboron compounds are inherently electron deficient and typically adopt a trigonal‐planar (sp 2 ‐hybridized) geometry with the empty p z orb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Three-coordinate boron-containing materials have attracted considerable attention over the last several decades due to the conjugation between the vacant po rbital on boron and the p electrons of conjugated systems.T his conjugationl eads to desirable optical and electronic properties that, in turn, enable applications in optoelectronics and sensing materials. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] For example, severalg roupsh ave shown that three-coordinate boron,a sa ne lectron-acceptor,c ombined with electron-donor groups, giving D-A systems, can exhibit thermally activated delayed fluorescence (TADF), which is favourable for organic light-emitting diode (OLED) devices. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Amongt hree-coordinate boranes,b orolesa re unique because of their 4p-electron five-membered-ring structure, which presents antiaromatic character,according to Hückel's rule.…”
Section: Introductionmentioning
confidence: 99%
“…Three-coordinate boron-containing materials have attracted considerable attention over the last several decades due to the conjugation between the vacant po rbital on boron and the p electrons of conjugated systems.T his conjugationl eads to desirable optical and electronic properties that, in turn, enable applications in optoelectronics and sensing materials. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] For example, severalg roupsh ave shown that three-coordinate boron,a sa ne lectron-acceptor,c ombined with electron-donor groups, giving D-A systems, can exhibit thermally activated delayed fluorescence (TADF), which is favourable for organic light-emitting diode (OLED) devices. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Amongt hree-coordinate boranes,b orolesa re unique because of their 4p-electron five-membered-ring structure, which presents antiaromatic character,according to Hückel's rule.…”
Section: Introductionmentioning
confidence: 99%
“…Three-coordinated boron-containing materials have attracted considerable attention over the last several decades due to the conjugation between the vacant p orbital on boron and π electrons of conjugated systems. This conjugation leads to desirable optical and electronic properties that, in turn, enable applications in optoelectronics and sensing materials. An emerging strategy of incorporation of boron in organic structures is the substitution of a CC bond with an isoelectronic and isosteric B–N unit (BN/CC isosterism). The isoelectronic nature between the BN and CC bonding arises from the fact that boron has three valence electrons and nitrogen has five valence electrons, and consequently, a B–N unit has the same valence electron count (that is, eight valence electrons) as a corresponding CC unit in which each carbon contributes four valence electrons; however, the strong dipole moment of the B–N unit makes it exhibit quite different properties. Since pioneering work on singly BN-substituted aromatic compounds by Dewar and co-workers in 1958, a large number of BN-doped PAHs have been developed which have exhibited potentials in applications of sensory materials, light-emitting materials, and organic electronics. Among them, in 2011, Nakamura and co-workers prepared a BN-doped PAH and studied the intrinsic hole mobility via time-resolved microwave conductivity measurements, which was higher than that of a carbon analog, meaning that BN-doped PAHs are potential candidates for organic electronic materials .…”
Section: Introductionmentioning
confidence: 99%
“…Boron is adjacent to carbon in the periodic table, which usually utilizes sp 2 hybridization to form neutral tricoordinated boron compounds, thus retaining an empty p orbital, showing obvious electron deficiency. The empty p orbital on boron is prone to form p−π* conjugation with lone-pair electrons or π-electrons of adjacent conjugated systems, which gives it unique optical and electronic properties. Many methods of incorporating boron into conjugated systems have been reported. Among them, using the isoelectric property between the B–N bond and the CC bond is an effective method to prepare boron-containing conjugated systems.…”
Section: Introductionmentioning
confidence: 99%